The Effect of Whatsapp Social Media as a Reminder of Compliance with Family Planning Acceptors in the Independent Practice of Midwife Ade Uum Sumiati Susandy - Ade Uum Susandy; Achmad Fauzi (STIKep PPNI Jawa Barat, 2023)
Aims : The purpose of this study was to determine the effect of whatsapp social media as a reminder of compliance with family planning acceptors in the independent practice of midwife Ade Uum Sumiati Susandy. Methods : The research design uses a quasi experiment with a post test control design. The study population was all family planning acceptors who were at the Independent Midwife Ade Uum Sumiati Susandy Practice, totaling 156 people using simple random sampling. The data collection tool used was the modified MMAS-8 (Morisky Medication Adherence Scale) questionnaire. Data analysis used chi-square. Results : The results showed that respondents who were given whatsApp social media as a reminder effectively increased family planning acceptor compliance with a p-value = 0.000 with a significance of p <0.05. Conclusion : WhatsApp social media as a reminder has a significant influence on increasing compliance with family planning acceptor visits at the independent midwife practice Ade Uum Sumiati Susandy.